Context Management for Distributed and Dynamic Context-Aware Computing - Rocha, Ricardo Couto Antunes; Endler, Markus; SpringerLink (Online service) (London : Springer London, 2012)
Research in context-aware computing has produced a number of middleware systems for context management. However, development of ubiquitous context-aware applications is still a challenge because most current middleware systems are still focused on isolated and static context-aware environments. Context-aware environments are inherently dynamic as a result of occasional additions or upgrade of sensors, applications or context inference mechanisms. Context Management for Distributed and Dynamic Context-Aware Computing proposes a novel architecture for context management based on the concept of context domains, allowing applications to keep context interests across distributed context management systems. The authors describe a distributed middleware that implements the aforementioned concepts, without compromising scalability and efficiency of context access.
Introduction -- Foundations of Context Management in Distributed and Dynamic Environments -- State of the Art -- Domain-based Context Management -- Usage Scenario -- Middleware for Context Management based on Context Domains -- Implementation and Evaluation -- Conclusions.
Keywords: Computer science; Computer Communication Networks; Computer Science; Computer Communication Networks; Computer Science, general